Synthesis and Physicochemical Studies of Iodide Complexes of Lanthanides and Yttrium with 4-Aminoantipyrine - John, Magi; Radhakrishnan, P.K. (Asian Journal of Chemistry, 2010)
A new series of the iodide complexes of lanthanides and yttrium with 4-aminoantipyrine (AAP) of the composition [Ln(AAP)4I2]I (where Ln═La, Pr, Nd, Sm and Gd) and [Ln(AAP)3I3] (where Ln═Y and Dy) were prepared and characterized by elemental, conductance, spectral (IR and electronic) and thermogravimetric analysis. AAP acts as a neutral monodentate ligand coordinating through the carbonyl oxygen. Only one of the iodines in the complexes of La, Pr, Nd, Sm and Gd is not coordinated. TG studies indicate a three stage decomposition with the formation of metal oxides above 520ºC in static air and a two-stage decomposition with the formation of metal iodides above 720ºC.